Analisis Kebutuhan Sistem Pendingin pada Ruang Kerja di PT. Fesco Offshore Kalimantan Timur - Saneta, Chelsea Orisa; Panjaitan, Jonery Hardianto; Matondang, Ridho Wiranata (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Cooling machines are quite well known to everyone, especially those in tropical areas. As is known, tropical areas have quite hot temperatures so that cooling devices are needed to cool the room. The importance of the cooling system in everyday life, both at home, in the office and in other places that require air conditioning. Therefore, the author is interested in conducting research entitled